2018
DOI: 10.1007/s10433-018-0486-z
|View full text |Cite
|
Sign up to set email alerts
|

Social networks and social activities promote cognitive functioning in both concurrent and prospective time: evidence from the SHARE survey

Abstract: The study aimed to investigate the role of social activities, social networks as well as socioeconomic status (SES)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 74 publications
(70 reference statements)
0
25
0
Order By: Relevance
“…In this way, knowledge can be pursued regarding what is actionable for health promotion and wellbeing improvement of elderly people in these Mediterranean countries. Maintaining and increasing functional capacity, maintaining or improving self-care, and fostering one's social network, and also social participation and integration [27], contribute to a longer, more independent, and self-sufficient quality of life [39] with an important impact on individual health status. At the policy level, infrastructure investments can be suggested to favor active aging of elderly people, such as recreation centers with a supply of cultural programs, physical training, and other activities which stimulate high cognitive involvement to enhance executive functions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this way, knowledge can be pursued regarding what is actionable for health promotion and wellbeing improvement of elderly people in these Mediterranean countries. Maintaining and increasing functional capacity, maintaining or improving self-care, and fostering one's social network, and also social participation and integration [27], contribute to a longer, more independent, and self-sufficient quality of life [39] with an important impact on individual health status. At the policy level, infrastructure investments can be suggested to favor active aging of elderly people, such as recreation centers with a supply of cultural programs, physical training, and other activities which stimulate high cognitive involvement to enhance executive functions.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, it is through cognitive functions that people perform most of the daily actions, even the simplest ones, such as driving a car or doing the shopping, and maintaining social relationships and social activities. There is abundant literature showing that cognitive functions can be enhanced and maintained through protective factors, which are linked to lifestyle [24][25][26] and quality of life [27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evans et al (2018) observed a decline in cognitive function in community members who had few ties to family or friends, whereas engaging in social and cognitive leisure activities in middle (Ihle et al, 2018) and older age (Fancourt and Steptoe, 2018) produced positive outcomes for cognition in later life. Furthermore, some research has even suggested that social engagement may be more important than cognitive function in reducing the degree of cognitive decline that occurs during aging (Miceli et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Being physically active and out-of-home mobility promote people's health (Faß and Schlesinger 2019), autonomy, identity and well-being, even in older age (Claßen et al 2014;Hamer et al 2014;Oswald and Konopik 2015;Wahl et al 2012). Active engagement, which includes active social participation and (active) mobility (Rowe and Kahn 1997), is an essential component of ageing well (Wahl et al 2012), reduces premature mortality (Maier and Klumb 2005;Pynnönen et al 2014;Thomas 2012) and morbidity (Hwang Han et al 2017) and increases cognitive function (Miceli et al 2018) and well-being (Bauman et al 2016). In particular, being with others or belonging to groups (e.g., friends or organised groups, such as clubs) is positively associated with better health and health-related outcomes (Burholt et al 2019;Tomaka et al 2006).…”
Section: Introductionmentioning
confidence: 99%